2016
DOI: 10.1002/2016sw001409
|View full text |Cite
|
Sign up to set email alerts
|

An improved empirical model of electron and ion fluxes at geosynchronous orbit based on upstream solar wind conditions

Abstract: A new empirical model of the electron fluxes and ion fluxes at geosynchronous orbit (GEO) is introduced, based on observations by Los Alamos National Laboratory (LANL) satellites. The model provides flux predictions in the energy range ~1 eV to ~40 keV, as a function of local time, energy, and the strength of the solar wind electric field (the negative product of the solar wind speed and the z component of the magnetic field). Given appropriate upstream solar wind measurements, the model provides a forecast of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 41 publications
2
66
0
Order By: Relevance
“…Hence, the composition of the inner magnetosphere during very long calm periods would be expected to become dominated by heavy ions. Following recent insights into composition changes and their relation to drift physics, (e.g., Denton, Reeves, et al, ; Ferradas et al, ; Zhang et al, , and references therein), coupled with the work described in the current study, we contend the implications of such composition changes remain under‐appreciated and in need of further exploration. For example, ion composition is known to be an essential variable when considering losses from the radiation belts, the growth of plasma instabilities, and the minimum resonant energy for wave‐particle interactions (e.g., Blum et al, , , ; Chen et al, ; Fuselier & Anderson, ; Gendrin et al, ; Gomberoff & Neira, ; Kozyra et al, ; MacDonald et al, ; MacDonald et al, ; Mouikis et al, ; Summers et al, ;7 Thorne et al, ).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Hence, the composition of the inner magnetosphere during very long calm periods would be expected to become dominated by heavy ions. Following recent insights into composition changes and their relation to drift physics, (e.g., Denton, Reeves, et al, ; Ferradas et al, ; Zhang et al, , and references therein), coupled with the work described in the current study, we contend the implications of such composition changes remain under‐appreciated and in need of further exploration. For example, ion composition is known to be an essential variable when considering losses from the radiation belts, the growth of plasma instabilities, and the minimum resonant energy for wave‐particle interactions (e.g., Blum et al, , , ; Chen et al, ; Fuselier & Anderson, ; Gendrin et al, ; Gomberoff & Neira, ; Kozyra et al, ; MacDonald et al, ; MacDonald et al, ; Mouikis et al, ; Summers et al, ;7 Thorne et al, ).…”
Section: Discussionsupporting
confidence: 63%
“…Previous work utilizing data from the HOPE instrument has demonstrated that the complex ion composition observations in the inner magnetosphere can be largely understood by simple drift physics and the charge‐exchange losses of the ions along their drift paths (cf. Denton, Henderson, et al, ; Fernandes et al, ; Ferradas et al, ; Henderson et al, ; Nosé et al, ; Yamauchi et al, ; Zhang et al, ). Such work demonstrates that complex features in the distributions can result from drift physics combined with charge‐exchange losses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of models, namely, the Fok Ring Current Model (FRC) (Fok & Moore, ; Fok et al, , ) and the Comprehensive Inner‐Magnetosphere Ionosphere (CIMI) model (Fok et al, , , ), run online at the Community Coordinated Modeling Center (http://ccmc.gsfc.nasa.gov/index.php) in near real time but without real‐time comparison with the observations. The purely empirical model for electron flux for 1 eV to 40 keV at GEO (Denton et al, , , ) based on LANL data (http://gemelli.spacescience.org/mdenton/) and dependent on the Kp index, daily F10.7 index, and − V SW B Z is not well suited for modeling of the specific events and of the fast variations of keV electrons due to its limited number of driving parameters. Another empirical model, the MSSL Electron Population Model, based on Cluster PEACE and EFW instrument data from 2001 to 2014 provides the omnidirectional 10 eV to 40 keV electron population parameterized by solar wind velocity and Kp index at MEO ( L = 4–6) and GEO ( L = 6–7).…”
Section: Introductionmentioning
confidence: 99%
“…These are typically fluid‐dynamical approximation models (e.g., Fok et al, ). Statistical models, which rely on dynamically fit linear and simple nonlinear filters. These typically have a more opaque interpretation than the models in (1) but tend to be easily fit and updated (e.g., Baker et al, ; Balikhin et al, ; Boynton et al, ; Denton et al, , ; Rigler & Baker, , ; Rigler et al, ). Note that some empirical models can still be based on physical principles, such as in Chen et al (). Models with forecasts driven by data‐mining techniques, typically neural networks.…”
Section: Introductionmentioning
confidence: 99%